Psychosocial assessment tools for children and young people aged 5–18 years: A rapid review of the literature. (12th January 2023) - McLean, Karen; O'Connor, Elodie; Ong, Rachel; Joseph, Corey; Skinner, Rachel; Goldfeld, Sharon
Abstract : Aim: Schools are a key platform for health promotion and a point of connection to local health‐care services, with an almost universal reach across the child and adolescent population. This study sought to determine whether validated psychosocial assessment tools exist for a school‐based nursing program that would assist in providing an initial health assessment to identify and understand the needs of children and young people referred to the nurse, with the outcome of appropriate connection to external health and wellbeing services. Methods: Rapid evidence assessment methodology was utilised to identify validated tools that could identify psychosocial concerns in children and young people aged 5–18 years. We identified articles from peer‐reviewed journals via three electronic bibliographic databases (PubMed, Embase and CINAHL). We then extended the search for evidence through a search of the grey literature. Results: From 3963 peer‐reviewed articles found in the database search, 10 relevant peer‐reviewed publications met inclusion criteria. In combination with 12 grey literature sources, 33 tools were identified. These included self‐report tools (typically for children aged 11 years and older), parent‐report and teacher‐report tools. We identified the six most promising psychosocial assessment tools. However, there was limited description about implementation within school‐based nursing programs. Conclusions: Several tools exist that show promise in assisting school‐based nursing programs to conduct preliminary psychosocial assessments for children and young people. The introduction of any tools into practice would require implementation guidance and evaluation, including how and when they should be used, and when referral and follow‐up is required.